EXPRESS: Attitudes and practices of veterinarians regarding feline pain management in Western versus Eastern Europe - Syed S. U. H. Bukhari; Sabrine Marangoni; Angel Almendros; Stelio PL Luna; Paulo Steagall (Journal of Feline Medicine and Surgery, 2026)
Objective This study aimed to report and compare attitudes and practices of veterinarians regarding feline pain management in Eastern and Western Europe. Methods A questionnaire was developed and divided into demographic data, drug availability/administration and pain management practices. The questionnaire went through content and face validity and was translated into several languages. An internet-based survey was created and responses were collected using a convenience sampling method. Data were analysed using multiple correspondence analysis. Results A total of 833 participants from Europe were included. Most respondents indicated good knowledge of acute pain assessment and recognition (n = 478; 57.4%). The Feline Grimace Scale was the most commonly used acute pain assessment instrument (n = 346; 41.5%). Chronic pain scoring instruments were not used by 48.5% (n = 404) of participants. Meloxicam and robenacoxib were the most used NSAIDs for chronic pain management. Limited knowledge of pain assessment, non-use of nonsteroidal anti-inflammatory drugs (NSAIDs) in cats undergoing surgery, and post-operative use of opioids were more closely associated with Eastern than Western Europe. Reported good knowledge of pain management, pre- and intraoperative use of NSAIDs, use of pain scales and pre-operative opioids, having a specialty diploma, and working in a cat-friendly practice were associated with Western than Eastern Europe. Conclusion and relevance Important regional differences were found regarding feline pain management across Europe. Continuing education, wider implementation of validated pain assessment tools, and improved access to analgesics may help reduce regional disparities and improve feline welfare.